The relationship of polymorphism with explosive forces in ACTN3, ACE, and UCP3 genes in soccer players - Atabas, Engin Gunes; Yapıcı Öksüzoğlu, Ayşegül; Turel, Samet; Akca, Hakan (Progress in Nutrition, 2020)
Study Objectives: The purpose of the study was to investigate the relationship of polymorphism with explosive forces in ACTN3, ACE, and UCP3 genes in soccer players. Methods: A total of 19 male soccer players and 9 sedentary voluntarily participated. Countermovement jump, squat jump, and standing long jump tests were applied to the subjects. On the same day, the subjects performed the jump tests twice again and the best score was recorded. Blood was drawn from subjects for Genomic DNA isolation. PCR products of ACTN3 and UCP3 genes Medical Genetics department genotypic differences between the groups were determined by analyzing with an automatic DNA sequencing system. Since taken non-parametric assumptions, it was analyzed by the Spearman test. Results: In subject group, a statistically significant relationship was found between all three jump performances in the subjects with ACTN3 RR and ACE ID genotype (p CMJ=0.04; SJ=0.04; SLJ=0.05) (p